2013
DOI: 10.11648/j.ajap.20130206.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Token Economy System Program and Physical Activity on Improving Quality of Life of Patients with Schizophrenia: A Pilot Study

Abstract: The aim of this pilot study was to examine the effect of an exercise and token economy system program on improving quality of life of patients with schizophrenia. Thirty (30) patients with schizophrenia separated in three groups (control group, an exercise observation with tokens group and an actual exercise with tokens group) of 10 individuals, took part in an eight weeks exercise program combining physical activity with token economy behavioral treatment. Data included the use of SF-36 Quality of Life Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The researcher concluded that there was an increase in self-care ability: eating was due to self-motivation, and because of the understanding received by the patient about what the researcher had taught so that it could be applied well by the patient. According to NANDA (2012) and Wilkinson (2011), self-care deficit: elimination is a barrier to the ability to perform, complete, or complete selfelimination activities/activities (Characteristic limitation of self-care deficit: elimination is the inability to perform proper elimination hygiene, flush the toilet , go to the toilet, take off or use clothes for elimination, get off the toilet or to sit/get up from the toilet, clean up after elimination.This is in accordance with research by Gholipur et.al (2011) and Kokaridas et.al (2013) that therapy behavior: the token economy is able to reduce negative symptoms and motivate clients with mental disorders.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The researcher concluded that there was an increase in self-care ability: eating was due to self-motivation, and because of the understanding received by the patient about what the researcher had taught so that it could be applied well by the patient. According to NANDA (2012) and Wilkinson (2011), self-care deficit: elimination is a barrier to the ability to perform, complete, or complete selfelimination activities/activities (Characteristic limitation of self-care deficit: elimination is the inability to perform proper elimination hygiene, flush the toilet , go to the toilet, take off or use clothes for elimination, get off the toilet or to sit/get up from the toilet, clean up after elimination.This is in accordance with research by Gholipur et.al (2011) and Kokaridas et.al (2013) that therapy behavior: the token economy is able to reduce negative symptoms and motivate clients with mental disorders.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in personal hygiene in patients was caused by the praise given in the form of reinforcement positive(rewards) given during the study. the research of Kokaridas, et al (2013), where the results of this pilot study show that in general the token economy is able to motivate schizophrenic patients to improve their quality of life.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…61 Through education, the capacity for culture change and hence, the acceptance of clinical exercise therapy within treatment facilities is likely to improve. Up-skilling existing health-professionals regarding basic principles of exercise prescription and evidence-based approaches to improving motivation 62,63 is essential, as is the need for dedicated exercise clinicians with expertise in exercise programming, to ensure that interventions are evidence-based and represent ‘best practice’.…”
Section: Challenges To Implementationmentioning
confidence: 99%
“…In this regard, only three studies examined the effect of a token economy system program combined with physical activity on improving psychological aspects of patients with schizophrenia, concerning quality of life (Kokaridas, Maggouritsa, Stoforos, et al, 2013) mood profile (Maggouritsa, Kokaridas, Theodorakis et al, 2014a) and self-esteem and body cathexis (Maggouritsa, Kokaridas, Stoforos, et al, 2014b).…”
Section: Physical Activity and Token Economy System Reviewmentioning
confidence: 99%